Competency Level Of National Educational Policy (Nep) Platforms And Other Modern Pedagogical Tools Used In Educational Institutions With Reference To Banglore - V, Anjali K; Sumathi, Dr.C. (Migration Letters, 2024)
In the realm of educational research, understanding the multitude of factors that influence academic success is of paramount importance. Educational institutions, policymakers, and stakeholders continuously seek to identify and comprehend these factors in order to enhance the quality and equity of educational outcomes. In pursuit of this understanding, this descriptive research study was conducted, focusing on the diverse and complex determinants of educational performance. The study is rooted in the principle that thorough exploration of these factors is essential for informed decision-making and evidence-based educational policies. In an attempt to gain comprehensive insights, this study utilized a sample of 150 participants, selected through simple random sampling, which ensures a cross-sectional representation of students and educators. By employing various statistical analysis tools, including percentage analysis, one-way ANOVA, and Structural Equation Modeling (SEM), this research aims to provide a nuanced understanding of the observed phenomena.